48.2k views
2 votes
Which value of x makes the equation
3(x - 6) = 8x - 3(3x + 7) true?

2 Answers

3 votes

Answer:

Just solve for "x"

3(x - 6) = 8x - 3(3x + 7)

3x -18 = 8x -9x -21

4x = -3

x = -3 / 4

Explanation:

User Hae
by
6.0k points
5 votes

Answer:

x = (-3)/4

Explanation:

Solve for x:

3 (x - 6) = 8 x - 3 (3 x + 7)

-3 (3 x + 7) = -9 x - 21:

3 (x - 6) = 8 x + -9 x - 21

Grouping like terms, 8 x - 9 x - 21 = (8 x - 9 x) - 21:

3 (x - 6) = (8 x - 9 x) - 21

8 x - 9 x = -x:

3 (x - 6) = -x - 21

Expand out terms of the left hand side:

3 x - 18 = -x - 21

Add x to both sides:

3 x + x - 18 = (x - x) - 21

x - x = 0:

3 x + x - 18 = -21

3 x + x = 4 x:

4 x - 18 = -21

Add 18 to both sides:

4 x + (18 - 18) = 18 - 21

18 - 18 = 0:

4 x = 18 - 21

18 - 21 = -3:

4 x = -3

Divide both sides of 4 x = -3 by 4:

(4 x)/4 = (-3)/4

4/4 = 1:

Answer: x = (-3)/4

User Mikey G
by
6.1k points